2021
DOI: 10.1186/s12879-021-05817-1
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Xpert MTB/RIF for TB diagnosis in the private sector: evidence from large-scale pilots in Patna and Mumbai, India

Abstract: Background Xpert MTB/RIF (Xpert) has been recommended by WHO as the initial diagnostic test for TB and rifampicin-resistance detection. Existing evidence regarding its uptake is limited to public health systems and corresponding resource and infrastructure challenges. It cannot be readily extended to private providers, who treat more than half of India’s TB cases and demonstrate complex diagnostic behavior. Methods We used routine program data coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“… 6 Existing evidence regarding its impact is primarily from the public sector, and studies examining the integration of Xpert into clinical decision-making are limited. 52 Compared to smear microscopy, this study found that Xpert increased the number and proportion of microbiologically confirmed TB case notifications and reduced the delay in treatment initiation. However, it did not significantly increase overall case notifications and did not have a significant impact on patient-relevant health outcomes such as mortality, TB-related morbidity, and successful treatment completion.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“… 6 Existing evidence regarding its impact is primarily from the public sector, and studies examining the integration of Xpert into clinical decision-making are limited. 52 Compared to smear microscopy, this study found that Xpert increased the number and proportion of microbiologically confirmed TB case notifications and reduced the delay in treatment initiation. However, it did not significantly increase overall case notifications and did not have a significant impact on patient-relevant health outcomes such as mortality, TB-related morbidity, and successful treatment completion.…”
Section: Discussionmentioning
confidence: 73%
“…However, it did not significantly increase overall case notifications and did not have a significant impact on patient-relevant health outcomes such as mortality, TB-related morbidity, and successful treatment completion. 52 These mixed findings are believed to be driven by high levels of empirical treatment, which may be partially reduced by a wider uptake of Xpert testing. 52 , 53 , 54 Inability to do microscopy or Xpert (as in sputum-scarce patients), substandard clinical training, and high likelihood of one-off encounters with patients might also drive the initiation of empirical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 A major challenge in India is the presence of a vast, fragmented private healthcare sector, which manages the majority of patients with TB in the country. [3][4][5] The past decade has seen increasing recognition of the importance of engaging effectively with this sector [6][7][8][9][10] : not only in notifying TB to public health authorities, but also in offering high-quality diagnostics and treatment adherence support for patients being managed by private providers. Early efforts to engage effectively with the private sector faced substantial challenges, principally arising from a lack of trust.…”
Section: Introductionmentioning
confidence: 99%
“…Though the government of India offers free quality-assured TB diagnosis and treatment through the National TB Elimination Programme (NTEP), which was earlier known as Revised National TB Control Program,2 more than half of TB cases are managed by private practitioners (PPs) in the country 3 4. Evidence shows that PPs rarely follow standard TB management guidelines5 6 and thus pose a threat of severe forms of drug-resistant TB.…”
Section: Introductionmentioning
confidence: 99%